Primary pure large cell neuroendocrine carcinoma of ovary: An extremely rare entity - Bhaker, Poonam; Dey, Pranab; Srinivasan, Radhika; Saha, Subhash Chandra (Annals of Pathology and Laboratory Medicine, 2014)
Primary large cell neuroendocrine carcinoma of ovary is an uncommon neoplasm with an aggressive biological behaviour. These carcinomas usually occur in association with epithelial-sex cord tumours; pure form being a rarity which can pose a diagnostic difficulty. A 42 year old female presented with a large abdominal mass and pain.Â  Computed tomography revealed a heterogeneously enhancing solid left ovarian mass. Differential diagnoses on histopathology included large cell neuroendocrine carcinoma, carcinoid tumour, hepatoid carcinoma and malignant steroid cell tumour, not otherwise specified (NOS). Positive neuroendocrine markers including CD56, chromogranin, and NSE facilitated a correct diagnosis of large cell neuroendocrine carcinoma. Primary ovarian large cell neuroendocrine carcinomas are under-recognized aggressive tumours and must be considered as a differential in undifferentiated ovarian tumours. Histologic features and a panel of immunohistochemical stains should lead to the correct diagnosis.